Biotechnology of the suspension cultivation of cells sensitive to mechanical effects - Karlash, Yuri; Povodzinsky, Vadim; Dumanskiy, Valentin (My University, 1992)
Investigated and introduced into industry is the technology of getting interferons in fermemers provided with vibration and pulsation mixing (after the autors' desing).The results obtained testify to the effectiveness of use of the vibration and pulsation mixing for biotechnology of the suspension cultivation of tissue and filamentuos cultures.
Keywords: fermentation equipment; suspension cultivation; tissue cultures; ферментаційне обладнання; суспензійне культивування; чутливі культури; кафедра біотехнології і мікробіології